A Rare Cause of Low Back Pain: Report of a Tailgut Cyst - E. A. Joyce; D. O. Kavanagh; D. C. Winter (Case Reports in Medicine)
Tailgut cysts, also known as retrorectal cystic hamartomas, are rare developmental abnormalities that typically occur in the retrorectal space. They are believed to arise from remnants of the embryonic hindgut (Hjermstad and Helwig, 1988). They can present as incidental findings during routine examination but over half of patients are thought to present with symptoms. MRI has become the modality of choice to image these frequently misdiagnosed cysts. Biopsy is not recommended. Complete intact surgical excision is advised to avoid the potential complications of these cysts which include infection, fistula formation, and the possibility of malignant transformation (Hjermstad and Helwig (1988), Mathis et al. (2010)). We describe the case of a 46-year-old female who presented with a 6-month history of low back pain. CT and MRI imaging demonstrated a complex retrorectal lesion with supralevator and infralevator components. This was removed using a combined transperineal and transabdominal approach. Histology confirmed a tailgut cyst.